EDUCATIONAL POSTER DESIGN FOR THE CAMPAIGN AGAINST SINGLE USE PLASTIC - Permata Bunda, Iva Aprevia; Murtiyoso, Onang (LPPM Univ. Ibn Khaldun Bogor, 2025)
In the face of increasingly pressing environmental issues related to the use of single-use plastics, this study aims to design an educational poster as an effective campaign tool to raise public awareness. The use of single-use plastics has become a major factor in environmental pollution, and previous research shows that public understanding and participation are still relatively low. Through an integrative visual communication design approach, this study examines elements in poster design that can attract attention, increase understanding, and encourage pro-environmental behavioral changes in the community. The research methodology used is a qualitative approach and literature study or document search covering various aspects of visual design and environmental campaigns. Successful design patterns include the use of attractive colors, easy-to-read typography, and visuals that have been presented. This study also discusses the importance of community involvement in poster design and continuous evaluation to increase campaign effectiveness. Thus, awareness and understanding of reducing single-use plastics are expected to motivate the community and strengthen existing sustainability initiatives in the community.